الهندسة المالية الإسلامية مدخل لتطوير المنتجات المالية الإسلامية - عزيزة بن سمينة (PROSPECTIVE RESEARCHES, 2023)
We will try through this paper to take in one of the most important challenges of the major worries economists and politicians alike, namely, financial risks and how to manage them, depending on the geometry of Islamic financial instrument suitable for innovative solutions and tools (products) of new financial strategies and flexible financial interact and benefit from the variables continuing in the global capital markets, regional and local, and combine routers Shara Islamic religion and considerations of economic efficiency, which acquires the subject of great importance, especially at this important stage, which has become the Islamic finance industry increasingly a focus of all global financial circles , as one of the tools entrusted with the play leadership role in the mobilization of resources and encourage a culture of saving among the communities on the one hand, on the other hand re-employment of these resources with the benefit of people.